Regularities of Encapsulation of Tolfenamic Acid and Some Other Non-Steroidal Anti-Inflammatory Drugs in Metal-Organic Framework Based on γ-Cyclodextrin - Ekaterina Delyagina; Anna Garibyan; Mikhail Agafonov; Irina Terekhova (MDPI AG, 2022)
Metal-organic frameworks based on cyclodextrins (CDs) have been proposed as promising drug delivery systems due to their large surface area, variable pore size, and biocompatibility. In the current work, we investigated an incorporation of tolfenamic acid (TA), a representative of non-steroidal anti-inflammatory drugs (NSAIDs), in a metal-organic framework based on γ-cyclodextrin and potassium cations (γCD-MOF). Composites γCD-MOF/TA obtained by absorption and co-crystallization methods were characterized using powder X-ray diffraction, low temperature nitrogen adsorption/desorption, scanning electron microscopy, and FTIR spectroscopy. It was demonstrated that TA loaded in γCD-MOF has an improved dissolution profile. However, the inclusion of TA in γ-CD reduces the membrane permeability of the drug. A comparative analysis of the encapsulation of different NSAIDs in γCD-MOF was performed. The impact of NSAID structure on the loading capacity was considered for the first time. It was revealed that the presence of heterocycles in the structure and drug lipophilicity influence the loading efficiency of NSAIDs in γCD-MOF.